A Proposed Model for Assessing Organisational Culture Towards Achieving Business Objectives - Salleh, Hafez; Abdul Aziz, Nurmadhiyah; Mohamed Sabli, Nor Azlinda; Kasim, Rozilah (Journal of Techno-Social, 2011)
Most of the traditional business performances measures are based on productivity and process criteria, which mainly focus on method of investment appraisal such as payback method, return on investment (ROI), cost-benefits analysis (CBA), net present value (NPV), internal rate of return (IRR). However, the measurement scales of business performance are not limited to those measures. One element that has strong correlation to the business performances is ‘organisational culture’. Many studies proved that one of the significant criteria for achieving desired business objectives is the right organisational culture within workplace. Basically, the measurement of organisational culture is reflecting on two distinct elements: organisational culture and business objectives. In broader perspective, an organisation is considered effective if it meets its business objectives. This paper aims to present and discuss the preliminary culture model to indicate the culture performance within organisational. The model has been developed through literature review, expert opinion and experience which is anticipated of being able to potentially measure the culture capability of organisations across industries to “successfully achieve business objectives”. The model is composed of six progressive stages of maturity that an organisation can achieve its culture performance. For each maturity stage, the model describes a set of characteristics that must be in place for the company to achieve each stage. The validity of the proposed model will be tested by a few case studies. The idea is to provide managers with a qualitative measurement tools to enable them to identify where culture improvements are required within their organisations and to indicate their readiness for achieving business objectives.